2012
DOI: 10.1075/ni.22.2.06yus
|View full text |Cite
|
Sign up to set email alerts
|

How do narrative and language skills relate to each other?

Abstract: Past studies on narratives have identified two main dimensions of narrative production: the story-related narrative quality, which relates to the narrative structure and evaluations, and the language-related quality, which relates to the appropriate use of linguistic devices that contribute to the overall discourse cohesion. Although studies on the language development of monolinguals and bilinguals have demonstrated the developmental nature of the two different narrative dimensions, little attention has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…In contrast, children who are dominant in one language may lack the necessary vocabulary and grammatical skills in their weaker language to support the use of macrostructure features in that language, even if they have previously acquired these features in their stronger language. This idea is supported by the work of Kang (2012) and Rezzonico et al (2016) discussed above. The children in Kang's (2012) study were reported to have stronger Korean abilities, so they may not have developed the linguistic skills needed in English to convey more advanced macrostructure features previously acquired in Korean; as such, there was no cross-language association.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…In contrast, children who are dominant in one language may lack the necessary vocabulary and grammatical skills in their weaker language to support the use of macrostructure features in that language, even if they have previously acquired these features in their stronger language. This idea is supported by the work of Kang (2012) and Rezzonico et al (2016) discussed above. The children in Kang's (2012) study were reported to have stronger Korean abilities, so they may not have developed the linguistic skills needed in English to convey more advanced macrostructure features previously acquired in Korean; as such, there was no cross-language association.…”
mentioning
confidence: 64%
“…At present, two studies have examined cross-language macrostructure associations concurrent with associations between microstructure and macrostructure in the narratives of young bilinguals, but their findings differ. Kang (2012) examined 5-to 6-year-old Korean-English bilinguals and found that English microstructure measures predicted children's production of English macrostructure; however, children's production of Korean macrostructure was not a significant predictor of English macrostructure when controlling for English narrative microstructure measures. Contrary to Kang's findings, Rezzonico et al (2016) examined 4-to 5-year-old Cantonese-English bilingual children and found that Cantonese macrostructure did predict English macrostructure after controlling for English microstructure measures.…”
mentioning
confidence: 99%
See 3 more Smart Citations